Recovered territory : a German-Polish conflict over land and culture, 1919-89 - Polak-Springer, Peter (Berghahn, 2015)
"Upper Silesia, one of Central Europe's most important industrial borderlands, was at the center of heated conflict between Germany and Poland and experienced annexations and border re-drawings in 1922, 1939, and 1945. In their interaction with--and mutual influence on--one another, political and cultural actors from both nations developed a transnational culture of territorial rivalry. Architecture, spaces of memory, films, museums, folklore, language policy, mass rallies, and archeological digs were some of the means they used to give the borderland a 'German'/'Polish' face. Representative of the wider politics of twentieth-century Europe, the situation in Upper Silesia played a critical role in the making of history's most violent and uprooting eras, 1939-1950"--Provided by publisher